Volatility of Companies with Low ESG Scores in the Indonesian Capital Market: Impact of Domestic and Global Factors - Asih, Kiki Nindya; Achsani, Noer A.; Novianti, Tanti; Manurung, Adler Haymans (Universitas Pendidikan Ganesha, 2024)
This study aims to explore the volatility connectedness between various categories of ESG scores of Indonesian companies with local and global market factors during the COVID-19 pandemic. We use daily price data of 42 Indonesian companies over the period from 2018 to 2022 and employ the GARCH model, further enriched by the Diebold-Yilmaz method, to analyze the spillover effect and connectedness. Companies with the lowest ESG category (D) exhibited the highest volatility throughout the observed period. All ESG categories experienced a significant increase in volatility during the COVID-19 pandemic. Meanwhile, companies with higher ESG categories (B) had the highest level of connectedness with domestic and global factors, both before and after the pandemic. In contrast, companies with the lowest ESG category (D) exhibited the lowest level of connectedness with domestic and global factors. The volatility spillovers indicate that both global (DJI) and domestic (LQ45) stock markets are the primary sources of spillovers for all ESG categories. This underscores the importance of understanding ESG category characteristics and market risk dynamics in ESG investment strategies. The study identifies significant differences between the risk profiles of ESG categories in the Indonesian capital market, with systematic risks affecting companies with high ESG ratings, while companies with low ESG ratings are more susceptible to idiosyncratic risks. These findings suggest the need for tailored diversification strategies in ESG investment and highlight the importance of considering these dynamics for investors, market regulators, and investment managers.